2016
DOI: 10.4028/www.scientific.net/msf.879.164
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Friction Behavior of AISI 52100 and D2 Steels Subjected to Ultrasonic Nanocrystalline Surface Modification (UNSM) Technique at a High Temperature

Abstract: In this study, two different AISI 52100 bearing and D2 tool steels were subjected to ultrasonic nanocrystalline surface modification (UNSM) technique at ambient and high temperature of 500 °C. The objective of this study is to characterize the microstructure and to investigate the effectiveness of UNSM technique on the friction and wear behavior of those steels. The friction and wear behavior of the specimens against AISI52100 bearing steel ball with a diameter of 10 mm was carried out using a micro-tribo test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The micro-hardness of the samples treated by UNSM at 300 • C, 500 • C, and 700 • C decreased across the volume by 5%, 24%, and 36%, respectively. These results are similar to those in a previous paper [19]. For the EPSM-treated samples (Figure 7b), the micro-hardness measurement results showed that the hardness of the samples mainly increased in the heat-treated zone for all three treatment regimes.…”
Section: Resultssupporting
confidence: 91%
“…The micro-hardness of the samples treated by UNSM at 300 • C, 500 • C, and 700 • C decreased across the volume by 5%, 24%, and 36%, respectively. These results are similar to those in a previous paper [19]. For the EPSM-treated samples (Figure 7b), the micro-hardness measurement results showed that the hardness of the samples mainly increased in the heat-treated zone for all three treatment regimes.…”
Section: Resultssupporting
confidence: 91%
“…Among them, there have been research cases in which UNSM has been applied to D2 steel. Amanov et al applied UNSM treatment to D2 steel at 500 °C and confirmed an improvement in performance [27]. Pyun et al analyzed the effects of the number and direction of UNSM treatment on the surface and mechanical characteristics of D2 and observed the surface changes between before and after heat treatment [28].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many studies have been conducted to improve the surface and mechanical characteristics of various materials by applying UNSM technology [15][16][17]. Amanov et al applied UNSM treatment to tool steel at 500 • C and confirmed an improvement in performance [18]. Pyun et al analyzed the effects of the number and direction of UNSM treatment on the surface and mechanical characteristics of D2 and observed the surface changes between before and after heat treatment [19].…”
Section: Introductionmentioning
confidence: 99%